2018
DOI: 10.1136/bmjsem-2018-000391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of overuse injuries in elite junior handball

Abstract: AimTo record overuse injuries among male junior handball players throughout a handball season.DesignProspective cohort study.MethodsTen Norwegian junior male handball teams (145 players aged 16–18 years) were followed for one 10-month season. All players were sent the Oslo Sports Trauma Research Center Overuse Injury Questionaire every second week to record overuse injuries located in the shoulder, elbow, lower back and knee. The relative burden of overuse injuries was calculated in each anatomical area repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 23 publications
6
61
5
1
Order By: Relevance
“…We found that the average season and average weekly prevalence of substantial shoulder problems in adolescent players was 23% and 6%, respectively. This is in line with the prevalence reported in previous studies on adolescent (94) and adult players in Norway (40,44,74) ( Table 3). Aasheim et al reported an average weekly prevalence of any and substantial shoulder problem of 17% and 7%, respectively.…”
Section: Prevalence and Persistence Of Shoulder Problemssupporting
confidence: 92%
See 4 more Smart Citations
“…We found that the average season and average weekly prevalence of substantial shoulder problems in adolescent players was 23% and 6%, respectively. This is in line with the prevalence reported in previous studies on adolescent (94) and adult players in Norway (40,44,74) ( Table 3). Aasheim et al reported an average weekly prevalence of any and substantial shoulder problem of 17% and 7%, respectively.…”
Section: Prevalence and Persistence Of Shoulder Problemssupporting
confidence: 92%
“…The most frequently reported injuries in adolescent handball are traumatic lower limb injuries, e.g. ankle, thigh and knee injuries, and hand/finger injuries (65,66,72,73,79,89,90,92,93,94) and overuse injuries in the shoulder and lower leg (72,90,93). An overview of injury distribution in adolescent handball is presented in Table 2.…”
Section: Injury Location and Types Of Injurymentioning
confidence: 99%
See 3 more Smart Citations